Does presidential debate bring optimism? A study of Indonesia’s 2024 pre-election year - Fidiana, Fidiana; Retnani, Endang Dwi; Widyawati, Dini (Research Papers in Economics and Finance, 2025)
The political future is inherently unpredictable, particularly in the run-up to elections. This article analyses whether such uncertainty matters. In this paper, we raise an interesting issue of the impact of political debate on the stock market of a developing country. Specifically, we investigate whether people’s economic expectations are conditional on their estimations of potential election outcomes. The subject of this study is the relationship between political events, including the 2024 presidential debate, and Indonesia’s financial markets. The authors analyse stock price movements of the 30 most actively traded issuers, as ranked by the Indonesia Stock Exchange, acknowledging that not all issuers trade daily in this emerging market. Using the Wilcoxon rank-sum test, we assess whether significant differences in investor responses exist before and after the debate periods (debates 1 to 5). According to the findings, investors believe that this event has no impact on their economic decisions, because candidate electability is dominated by incumbent candidates, so it is assumed that there will be no significant changes in financial policy. Therefore, investors appear relatively indifferent to the election dynamics during this period. Overall, the results show that Indonesian people anticipate election outcomes.